Rare Earth Element Behavior in a Sandy Subterranean Estuary of the Southern North Sea - Paffrath, Ronja; Pahnke, Katharina; Behrens, Melanie K.; Reckhardt, Anja; Ehlert, Claudia; Schnetger, Bernhard; Brumsack, Hans-Jürgen (Frontiers in Marine Science, 2020)
The use of rare earth elements (REEs) as tracers for oceanic processes requires knowledge and quantification of their sources and sinks. Submarine groundwater discharge (SGD) has been suggested to be a potentially important source of REEs and other trace elements to the ocean. To investigate the processes affecting REEs in a subterranean estuary (STE) of a sandy beach system and their contribution to coastal waters of the southern North Sea, we analyzed dissolved REE concentrations in beach pore waters, coastal seawater and fresh groundwater on the barrier island Spiekeroog, German North Sea. The pore waters show variable REE concentrations (Neodymium between 6 and 54 pmol/kg), generally increasing from the upper beach to the shoreline. At the upper beach, mixing of coastal pore water with rainwater and scavenging lead to lower REE concentrations than in coastal seawater and high heavy (HREE) over light (LREE) REE ratios. Close to the low water line, the REE concentrations increase, partly exceeding seawater concentrations and showing a positive deviation from conservative mixing, with shale-normalized light and middle REE-enriched patterns. This is due to the release of light and middle REEs from degrading particulate organic material and potentially dissolution of Fe/Mn-oxides under reducing conditions. Reducing conditions are further supported by the change from a negative Ce-anomaly at the upper beach to no anomaly close to the low water line. Net SGD fluxes of both fresh groundwater and recirculated seawater are a source of light, middle and heavy REEs to the ocean, with a higher contribution of LREEs than HREEs compared to seawater. However, the total amount of REEs added to the North Sea by SGD from the East Frisian Islands is still ~500 times smaller than input from nearby rivers. An anthropogenic Gd signal higher than previously reported is present throughout the pore waters and seawater, indicating increasing accumulation of anthropogenic Gd in the coastal marine environment.